2020
DOI: 10.1111/anu.13049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary isoleucine level on growth, protein retention efficiency, haematological parameter, lysozyme activity and serum antioxidant status of fingerlingChanna punctatus(Bloch)

Abstract: Isoleucine requirement of fingerling Channa punctatus (6.74 ± 0.09 g) was estimated by feeding seven trial diets (450 g/kg CP, 14.73 kJ/g DE) containing 3.8, 7.5, 11.3, 15.1, 19.3, 23.2 and 27.4 g/kg of isoleucine for 12 weeks. Growth and haematological parameters increased with the increasing concentrations of dietary isoleucine up to 16 g/kg. Carcass protein and fat increased significantly with the increasing concentrations of dietary isoleucine up to 16 g/kg and then stabilized. Moisture content showed reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 107 publications
4
16
0
Order By: Relevance
“…In present result, dietary Ile signi cantly up-regulated muscle protein content. Similar results were observed in ngerling spotted snakehead [14], grass carp [9], and Nile tilapia [59]. Previous studies have observed that IGF1-PI3K-AKT acts a positive regulator in protein synthesis in mammals [77].…”
Section: Dietary Ile Improved Muscle Protein Depositionsupporting
confidence: 86%
“…In present result, dietary Ile signi cantly up-regulated muscle protein content. Similar results were observed in ngerling spotted snakehead [14], grass carp [9], and Nile tilapia [59]. Previous studies have observed that IGF1-PI3K-AKT acts a positive regulator in protein synthesis in mammals [77].…”
Section: Dietary Ile Improved Muscle Protein Depositionsupporting
confidence: 86%
“…The Ile, one of BCAA, have been reported the importance of effecting fish growth performance [ 9 , 14 , 59 ]. Fish growth is mainly determined by muscle growth, which constitutes the major edible sources of the fillet [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional content was mainly reflected by muscle protein and lipid contents. Emerging shreds of evidence have shown that dietary Ile could increase muscle protein and lipid contents of grass carp ( Ctenopharyngodon idella ) [ 9 ] and fingerling spotted snakehead ( Channa punctatus ) [ 14 ]. These results provided possible evidence that dietary Ile could affect muscle nutritional content and merit further study.…”
Section: Introductionmentioning
confidence: 99%
“…Six experimental diet were produced as follows: minimum level of Ile with minimum level of Val (LI‐LV), minimum of Ile with medium of Val, minimum of Ile with maximum of Val, maximum of Ile with minimum of Val (HI‐LV), maximum of Ile with medium of Val, maximum of Ile with maximum of Val (HI‐HV). Crystalline amino acid (CAA) mixture, 10% casein, 5% gelatin, and 20% fishmeal were supplemented to these six experimental diets to provide an amino acid profile in associated with 50% whole body protein of Japanese flounder (shown in Table 2; Alam et al., 2007; Han et al., 2013a; Sharf & Khan, 2020). And dispensable amino acid were supplemented to these six experimental diets to maintain it as isonitrogenous diet (Han, Koshio, et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Val is another BCAAs which plays an important role in certain biochemical reactions and the growth performnance of monogastric animals (Bae et al., 2012; Sharf & Khan, 2020). Previous studies already established the optimum requirements of Val in aquatic animals, for Japanese flounder, the optimal requirement of Ile is 2.5% of protein (Sharf & Khan, 2020). Moreover, Val was reported to increase the growth of juvenile Jian carp ( Cyprinus carpiovar .…”
Section: Introductionmentioning
confidence: 99%